Genomic and clinical predictors of lacosamide response in refractory epilepsies. Issue 4 (25th September 2019) - Heavin, Sinéad B.; McCormack, Mark; Wolking, Stefan; Slattery, Lisa; Walley, Nicole; Avbersek, Andreja; Novy, Jan; Sinha, Saurabh R.; Radtke, Rod; Doherty, Colin; Auce, Pauls; Craig, John; et al.
Abstract: Objective: Clinical and genetic predictors of response to antiepileptic drugs (AEDs) are largely unknown. We examined predictors of lacosamide response in a real‐world clinical setting. Methods: We tested the association of clinical predictors with treatment response using regression modeling in a cohort of people with refractory epilepsy. Genetic assessment for lacosamide response was conducted via genome‐wide association studies and exome studies, comprising 281 candidate genes. Results: Most patients (479/483) were treated with LCM in addition to other AEDs. Our results corroborate previous findings that patients with refractory genetic generalized epilepsy (GGE) may respond to treatment with LCM. No clear clinical predictors were identified. We then compared 73 lacosamide responders, defined as those experiencing greater than 75% seizure reduction or seizure freedom, to 495 nonresponders (<25% seizure reduction). No variants reached the genome‐wide significance threshold in our case‐control analysis. Significance: No genetic predictor of lacosamide response was identified. Patients with refractory GGE might benefit from treatment with lacosamide.